Targeted next-generation sequencing of locally advanced squamous cell carcinomas of the head and neck reveals druggable targets for improving adjuvant chemoradiation. (April 2016) - Tinhofer, I.; Budach, V.; Saki, M.; Konschak, R.; Niehr, F.; Jöhrens, K.; Weichert, W.; Linge, A.; Lohaus, F.; Krause, M.; Neumann, K.; Endris, V.; et al.
Abstract: Background: Despite clear differences in clinical presentation and outcome, squamous cell carcinomas of the head and neck (SCCHN) arising from human papilloma virus (HPV) infection or heavy tobacco/alcohol consumption are treated equally. Next-generation sequencing is expected to reveal novel targets for more individualised treatment. Patients and methods: Tumour specimens from 208 patients with locally advanced squamous cell carcinoma of the hypopharynx, oropharynx or oral cavity, all uniformly treated with adjuvant cisplatin-based chemoradiation, were included. A customised panel covering 211 exons from 45 genes frequently altered in SCCHN was used for detection of non-synonymous point and frameshift mutations. Mutations were correlated with HPV status and treatment outcome. Results: Mutational profiles and HPV status were successfully established for 179 cases. HPV– tumours showed an increased frequency of alterations in tumour suppressor genes compared to HPV+ cases ( TP53 67% versus 4%, CDKN2A 18% versus 0%). Conversely, HPV+ carcinomas were enriched for activating mutations in driver genes compared to HPV– cases ( PIK3CA 30% versus 12%, KRAS 6% versus 1%, and NRAS 4% versus 0%). Hotspot TP53 missense mutations in HPV– carcinomas correlated with an increased risk of locoregional recurrence (hazard ratio [HR] 4.3, 95% confidence interval [CI] 1.5–12.1, P  = 0.006) and death (HR 2.2, 95% CI 1.1–4.4, P  = 0.021). In HPV+ SCCHN, driver gene mutations were associated per trend with a higher risk of death (HR 3.9, 95% CI 0.7–21.1, P  = 0.11). Conclusions: Distinct mutation profiles in HPV– and HPV+ SCCHN identify subgroups with poor outcome after adjuvant chemoradiation. Mutant p53 and the phosphoinositide 3-kinase pathway were identified as potential druggable targets for subgroup-specific treatment optimisation. Highlights: SCCHN tumor sequencing is useful for outcome prediction of adjuvant chemoradiation Unfavourable subgroup of tobacco-related SCCHN displays hotspot TP53 mutations PIK3CA, KRAS and NRAS mutations in HPV+ SCCHN are associated with reduced survival. Mutant p53 and the phosphoinositide 3-kinase pathway represent druggable targets.